Research Progress on Water–Fertilizer Coupling and Crop Quality Improvement and Its Implication for the Karst Rock Desertification Control - Tinghui Hu; Kaiping Li; Kangning Xiong; Jun Wang; Shan Yang; Zhifu Wang; Ajuan Gao; Xiao Yu (Agronomy, 2022)
An important problem currently faced by karst rocky desertification management is the degradation of vegetation fruits, which encourages the search for a solution for the sustainable growth of vegetation. Water and fertilizer are key factors affecting crop quality (the formation of soluble solids, protein, amino acids, soluble sugar content, etc.). A comprehensive review of research related to water–fertilizer coupling and crop quality improvement may be beneficial for rocky desertification control. This study analyzed 427 related papers, and the results showed that: (1) the number of published papers showed an “S” curve growth trend over time, indicating that research in the field of water–fertilizer coupling has entered a mature stage after rapid growth, yet it is still in the initial stage in karst areas; (2) the research was mainly theoretical, but also included technology research and development, model construction, demonstration and extension, and monitoring and evaluation; (3) except for research related to greenhouse facilities, the research areas are mainly located in arid and semi-arid regions. The study further revealed (4) the frontier theory of water–fertilizer coupling and crop quality research. Finally, it was found that the theoretical and technical studies related to water–fertilizer coupling and crop quality improvement in karst areas are insufficient. Whether the existing theories and techniques are applicable to karst areas needs further verification. In addition to the areas of selecting germplasm with high water/fertilizer utilization efficiency and tolerance to rocky desertification, further improvement in the dynamic model of water–fertilizer coupling and the construction of a more applicable water–fertilizer coupling model could also be future research hotspots.